Hak Asasi Manusia Mengenai Hak-Hak Tersangka Dalam Proses Acara Pidana - Putri Meutia Khairani; Taun (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
Human rights are the bedrock of an individual's dignity and freedom. The concept of human rights was born out of a global awareness of the need to protect people from injustice and abuse of power. In the context of criminal law, these rights play a very important role. When a person is involved in the judicial process, their rights must be protected so that they get fair treatment. This research aims to examine what rights are owned by suspects in the criminal procedure process. This research uses normative juridical method. The normative juridical method is an approach used to understand and analyze written legal norms. The result of this research is that the suspect has rights that are divided into several processes